Modelling and forecasting oil prices: The role of asymmetric cycles - Jesus Crespo Cuaresma; Adusei Jumah; Sohbet Karbuz (University of Innsbruck, Department of Public Finance, 2007)
We propose a new time series model aimed at forecasting crude oil prices. The proposed specification is an unobserved components model with an asymmetric cyclical component. The asymmetric cycle is defined as a sine-cosine wave where the frequency of the cycle depends on past oil price observations. We show that oil price forecasts improve significantly when this asymmetry is explicitly modelled.
Keywords: C22; O13; C53; 330; oil price; forecasting; nonlinear time series analysis; asymmetric cycles; Ölpreis; Zeitreihenanalyse; Nichtlineares Verfahren; Prognoseverfahren; Theorie